Agricultural Policy Dynamics and the Issue of Social Protection in Nepal - Pokharel, Bandana; Timsina, Tirtha Raj (Journal of Social Protection, 2024)
The agricultural sector in Nepal has seen a decline in its contribution to the Gross Domestic Product (GDP), leading to rural-to-urban migration and increased poverty and livelihood vulnerabilities in rural areas. Despite various policy interventions, the sector struggles with low productivity, challenges posed by climate change, and limited access to resources especially among the marginalised groups. This study examines Nepalese agricultural policy framework through the lens of social protection. Using a comprehensive review of secondary sources, the research highlights the gaps in policy implementation. Findings underscore the need for integrated approaches that combine agricultural interventions with social protection measures, such as cash transfers and crop insurance, to address vulnerabilities and improve food security which is eventually possible through the efforts of agricultural modernization that enhance productivity and resilience in rural communities.